Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{7}{4}-x.\frac{3}{4}=\frac{5}{19}\)
\(\Rightarrow1+\frac{3}{4}-x.\frac{3}{4}=\frac{5}{9}\)
\(\Rightarrow\frac{3}{4}.\left(1-x\right)=\frac{5}{9}-1=-\frac{4}{9}\)
\(\Rightarrow1-x=-\frac{4}{9}:\frac{3}{4}=-\frac{16}{27}\)
\(\Rightarrow x=1-\left(-\frac{16}{27}\right)=1+\frac{16}{27}=1\frac{16}{27}\)
(3/8 + x * 3/2 ) : 65/4 = 1
3/8 + x* 3/2 = 1 * 65/4
3/8 + x* 3/2 = 65/4
x* 3/2 = 65/4 - 3/8
x* 3/2 = 127/8
x = 127/8 : 3/2
x = 127/12
2x + 3x + 4x = 450
=> ( 2 + 3 + 4 )x = 450
=> 9x = 450
=> x = 50
\(4\times x^3+15=47\)
\(4\times x^3=32\)
\(x^3=8\)
\(x=2\)
\(\frac{3}{4}.\frac{12}{7}+x=\frac{5}{2}\)
\(\frac{3.3}{1.7}+x=\frac{5}{2}\)
\(\frac{9}{7}+x=\frac{5}{2}\)
\(x=\frac{5}{2}-\frac{9}{7}\)
\(x=\frac{35}{14}-\frac{18}{14}\)
\(x=\frac{17}{14}\)
x + \(3\frac{1}{2}\)+ x = \(24\frac{1}{4}\)
x + x = \(24\frac{1}{4}-3\frac{1}{2}\)
x X 2 = \(\frac{97}{4}-\frac{7}{2}\)
x X 2 = \(\frac{83}{4}\)
b ) x X \(\frac{7}{x}\)= 7
\(\frac{x}{1}\)x \(\frac{7}{x}\)= 7
= > x = 1
(x - \(\dfrac{2}{3}\))x3 = 3/4
x - 2/3 = 3/4 : 3
x - 2/3 = 1/4
x = 1/4 + 2/3
x = 11/12
\(\left(x-\dfrac{2}{3}\right)\times3=\dfrac{3}{4}\\ \Rightarrow x-\dfrac{2}{3}=\dfrac{3}{4}:3\\ \Rightarrow x-\dfrac{2}{3}=\dfrac{1}{4}\\ \Rightarrow x=\dfrac{1}{4}+\dfrac{2}{3}\\ \Rightarrow x=\dfrac{3+8}{12}\\ \Rightarrow x=\dfrac{11}{12}\)